Deconstructing North Sámi sensive verbs - Julien, Marit (Glossa: a journal of general linguistics, 2021)
North Sámi has a class of derived verbs called sensive verbs. Descriptively, these verbs are formed by adding the suffix /ʃ/ to an adjectival or nominal base, and the resulting verb means ‘find [object] (too) ADJECTIVE/NOUN’. In this paper it is argued that the sensive verbs do not involve any psychological verb, and the suffix is not specified as “sensive” in the lexicon. Rather, the suffix is specified as a realisation of a stative verbaliser in a transitive structure. The interpretation of the verb and the experiencer role of the subject follow from this specification in combination with the syntax of the verb phrase as a whole, which has a stative verbaliser and a Voice head on top of a minimal aP or nP. Other vocabulary items that could spell out the stative verbaliser are prevented from appearing in the sensive verb phrase, since the conditions for inserting them are not met. The consequence is that the suffix /ʃ/ is restricted to sensive verbs.